2013
DOI: 10.1002/jgrg.20081
|View full text |Cite
|
Sign up to set email alerts
|

Losses of NO and N2O emissions from Venezuelan and other worldwide tropical N‐fertilized soils

Abstract: [1] N fertilization significantly increases N 2 O and NO soil fluxes to the atmosphere. In spite of the expansion of agricultural activities in tropical managed soils from the developing world, there is little information about the loss of applied nitrogen (LAN) as NO and N 2 O from these areas. In this work, we determined LAN-N 2 O and LAN-NO from different crops during the growing season at a sandy soil experimental field and two active farms with loamy and clay soils, respectively. Tillage (T) and no-tillag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…A previous investigation suggested that the denitrification process was the main source of N 2 O emission in subtropical forest soils [ Zhang et al , ]. Marquina et al [] have also reported that the loss of applied nitrogen as N 2 O and NO is higher than the Intergovernmental Panel on Climate Change default value in cropping systems of the tropical savanna region.…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation suggested that the denitrification process was the main source of N 2 O emission in subtropical forest soils [ Zhang et al , ]. Marquina et al [] have also reported that the loss of applied nitrogen as N 2 O and NO is higher than the Intergovernmental Panel on Climate Change default value in cropping systems of the tropical savanna region.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with temperate and subtropical regions, the studies concerning N 2 O emissions from tropics are currently limited (Mosier et al 2004;Marquina et al 2013). To make a global comparison, we compiled the available literature data (Fig.…”
Section: Banana Yield and Yield-scaled N 2 O Emissionmentioning
confidence: 99%
“…Banana cultivation is characterized by high N fertilization rates, frequent irrigation, and high temperatures (Veldkamp and Keller 1997;Irizarry et al 2002). The N application rate (in the form of mineral fertilizer and poultry manure) is as high as 500-1300 kg N ha −1 (Al-Harthi and Al-Yahyai 2009; Yao et al 2009;Al-Busaidi 2013), which is significantly higher than that used in other food crops (e.g., rice, wheat, and maize) (Watanabe et al 2000;Weitz et al 2001;Khalil et al 2002;Marquina et al 2013). In addition, multiple topdressings in combination with irrigation are also utilized during the banana-growing season (Veldkamp and Keller 1997).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations